Early predictors of antiviral treatment response in liver transplant recipients with recurrent hepatitis C genotype 1. Issue 10 (12th March 2014) - Campos‐Varela, I.; Esteban, J. I.; Bes, M.; Caralt, M.; Allende, H.; Rodríguez‐Frías, F.; Salcedo, M. T.; Sauleda, S.; Charco, R.; Guardia, J.; Esteban, R.; Castells, L.
Summary The success of current antiviral treatment for hepatitis C virus (HCV) recurrence in liver transplant (LT) recipients remains limited. We aimed at evaluating the value of IL28B genotype and early viral kinetics to predict response to standard treatment in the transplant setting. We retrospectively evaluated 104 LT recipients treated for HCV genotype 1 recurrence between 2001 and 2010. Baseline variables, including IL28B genotype, and early viral kinetics were compared among patients who did or did not achieve a sustained virological response (SVR). Logistic regression analyses of candidate variables were conducted to generate a reliable predictive model based on the minimum set of variables. Twenty‐nine (28%) achieved an SVR. On multivariate analysis, the magnitude of HCV RNA decline at 4 weeks (OR: 3.74, 95% CI: 1.64–9.39; P = 0.003) and treatment compliance (OR: 35.27, 95% CI: 3.35–365.54; P = 0.003) were the only independent predictors of SVR. Favourable recipient IL28B genotype significantly correlates with virological response at week 4 (OR 3.23; 95% CI, 1.12–9.15; P = 0.03). By logistic regression analysis, a model including donor age, recipient rs12979860 genotype and viral load at 4 weeks showed the best predictive value for SVR with an area under the receiver operating curve of 0.861. Favourable recipient IL28B genotype strongly correlates with the viral response at week 4 which is the strongest predictor of response. The combination of recipient IL28B genotype and donor age with the week 4 response reliably estimates the probability of SVR early on‐treatment and may facilitate therapeutic strategies incorporating new antiviral agents.